Interaction between the voltage‐droop and the frequency‐droop control for multi‐terminal HVDC systems. Issue 6 (1st April 2016) - Akkari, Samy; Dai, Jing; Petit, Marc; Guillaud, Xavier
Abstract : Multi‐terminal DC systems must provide a high level of reliability and may have to support the interconnected AC grids. This can be achieved by providing AC/DC converters with a dual controller combining both the voltage‐droop and the frequency‐droop control techniques. In this article, the coupling between those droops is theoretically investigated and quantified, and a proposed corrected value of the frequency‐droop parameter allows the system to comply with the TSO's requirements with regards to the frequency support of the AC grids despite the unintended interaction of the two droops. A dynamic frequency‐droop parameter is then proposed to also cope with the controller limits. Finally, an electromagnetic transient study of a five‐terminal HVDC grid is performed to validate the theoretical results.